If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24 = m + 60 Reorder the terms: 24 = 60 + m Solving 24 = 60 + m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1m' to each side of the equation. 24 + -1m = 60 + m + -1m Combine like terms: m + -1m = 0 24 + -1m = 60 + 0 24 + -1m = 60 Add '-24' to each side of the equation. 24 + -24 + -1m = 60 + -24 Combine like terms: 24 + -24 = 0 0 + -1m = 60 + -24 -1m = 60 + -24 Combine like terms: 60 + -24 = 36 -1m = 36 Divide each side by '-1'. m = -36 Simplifying m = -36
| -5.46+x=-.3 | | -4(3x+7)=-76 | | x^2-4x-7=3cosx | | 196x=196 | | 7x/3=35 | | 2/3×-7=4×-8 | | -2y+9=-27 | | 2x-51=19 | | -3+6x=67-4 | | (3x+11)+(10x-12)=90 | | 3d-12+5d=8d-12 | | 17cosx-15=0 | | (-2.7)+4.9x=-13.2 | | w-(-8)=-15 | | 2x+6-x=44-15+35 | | 3(x-2)+5=4 | | x^2-4x-7=2cosx | | 8/1*-7/2 | | 9(8d+7)= | | -8(x-3)=-72 | | 4x+3x+x=-152 | | -1/5*2/9 | | n-22=15 | | 5x+1=6x+9 | | 2.43+x=-.3 | | 2h-14=-15h | | -3(3+7p)=138 | | fx=(4x-7)+(x-x+3) | | 3y+19=11y-21 | | Y=-2x^2-21x+11 | | 5550000x+2085000000=25000000 | | (b+10)(3b)b= |